Jovens de Gaza defendem que novo instrumento deve desburocratizar a obtenção de DUAT e combater a expropriação de terras pelas elites - Emídio Beula (Centro Para Democracia e Desenvolvimento (CDD), 2021)
Falando em representação da Governadora da Província de Gaza, a Directora Provincial de Cultura e Turismo denunciou o velho problema de usurpação e acumulação de terra para fins de especulação latifundiária. Trata-se de uma prática comum em Moçambique em que as elites económicas e políticas se apropriam de terras valiosas e ficam à espera do melhor momento para fazer a transacção, preferencialmente com o capital estrangeiro. A representante da Governadora de Gaza disse que esta prática prejudica mais as mulheres que vivem nas zonas rurais por constituírem o grupo que mais usa a terra para a actividade agrícola. A Directora Provincial de Cultura e Turismo em Gaza saudou a iniciativa do CDD de auscultar a juventude sobre a revisão da Política Nacional de Terras, defendendo que, sendo a maioria da população, os jovens devem se apropriar do debate para influenciar a concepção de futuros instrumentos políticos e legais sobre o uso de terras.
Keywords: #Reporting & Media / Reportagem & Mídia; *indexed; *tagged; DUAT (Direito do uso e aproveitamento da terra) / Land Use and Benefit Right; G - Mozambique / Moçambique; GP - Gaza; L - portuguese / português; agriculture / agricultura; governance / governação; land governance / gestão de terra; youth / juventude

Jovens de Inhambane defendem que futura legislação deve estabelecer um prazo de até 15 dias para resposta ao pedido do DUAT - Emídio Beula (Centro Para Democracia e Desenvolvimento (CDD), 2021)
Depois da cerimónia inaugural de quinta-feira na Província de Gaza, ontem, sexta-feira, 07 de Maio, foi a vez de Inhambane acolher o debate público no âmbito da auscultação de jovens sobre a revisão da Política Nacional de Terras. Falando na abertura da cerimónia, o Director dos Serviços Provinciais do Ambiente, em representação da Secretária de Estado da Província de Inhambane, defendeu que um dos desafios que a Inhambane enfrenta é o aumento do número de população perante um recurso terra que não é renovável, aliado aos desafios decorrentes das mudanças climáticas que demandam uma compensação da biodiversidade. O Director dos Serviços Provinciais do Ambiente de Inhambane falou também da emergência dos megaprojectos que, para o seu desenvolvimento, precisam do recurso terra. “A iniciativa do CDD de auscultar jovens sobre a revisão da Política Nacional de Terras constitui uma exaltação da cidadania. Todos nós, como moçambicanos, nas nossas comunidades, organizações, temos esta ímpar oportunidade de participar no melhoramento da nossa política de terras”.
Keywords: #Reporting & Media / Reportagem & Mídia; *indexed; *tagged; DUAT (Direito do uso e aproveitamento da terra) / Land Use and Benefit Right; G - Mozambique / Moçambique; GP - Inhambane; L - portuguese / português; agriculture / agricultura; governance / governação; land governance / gestão de terra; youth / juventude

Estimating the cost of implementing a facility and community score card for maternal and newborn care service delivery in a rural district in Uganda - Ssebagereka, Anthony; Apolot, Rebecca Racheal; Nyachwo, Evelyne Baelvina; Ekirapa-Kiracho, Elizabeth (International Journal for Equity in Health, 2021)
This paper aimed at estimating the resources required to implement a community Score Card by a typical rural district health team in Uganda, as a mechanism for fostering accountability, utilization and quality of maternal and child healthcare service.
Keywords: #Reviews & Framing / Revisões e Organização; *indexed; *tagged; G - Rest of the World / Resto do Mundo; Health PEA; L - english / inglês; access to services / acesso a serviços; accountability / responsabilização; community scorecard (CSC) / cartão de pontuação comunitária (CPC); gender / género; health - maternal and child / saúde - materno-infantil; health / saúde; youth / juventude

Innovative Finance for Employment: The Potential for Women and Urban Youth - MUVA; Social Finance Ltd (MUVA and Social Finance Ltd, 2021)
The need for female economic empowerment in Mozambique is clear; just 24% of women have access to wage employment, versus 50% of men. The situation is worse still in urban settings where 19-24-year-old women have the highest unemployment rates in the country. The national rate of formal employment is approximately 13%, and large scale formal job creation in the Oil and Gas sector is yet to materialise. Despite impressive economic growth in recent years, 50% of Mozambicans are still living in poverty and social and economic inequalities are continuing to grow. The challenges faced by disadvantaged urban youth and women (DUYW) are severe; without deliberate intervention to address the constraints facing them, this trend is set to worsen. In light of this challenge, MUVA commissioned a scoping study to assess the potential of innovative financing models to support the economic empowerment of disadvantaged urban youth and women. Innovative finance is a broad spectrum of mechanisms that offer an alternative to traditional activity based grant funding. It can include investment capital seeking a return, but also encompasses results based financing and broader risk mitigation mechanisms. If done correctly, innovative finance can support good interventions to better tackle entrenched social issues, by sharpening incentives, creating accountability for results, addressing specific barriers in the system, shifting where risk is held and fostering adaptive management. The study identified four innovative financing models that have the potential to enable disadvantaged urban youth and women in Mozambique to access economic opportunities. Some focus more on the supply side, working primarily with DUYW to improve their skills, employability and facilitate entry into the workforce. Others focus on the demand side, working with enterprises to enable them to scale, improve gender practices and encourage them to employ DUYW. Two of the shortlisted models sit across both demand and supply.
Keywords: G - Mozambique / Moçambique; L - english / inglês; employment / emprego; empowerment / empoderamento; gender / género; private sector / setor privado; urbanization / urbanização; youth / juventude

Jovens moçambicanos descontentes com falta de oportunidades (DW.COM, 2020)
No Dia Mundial da Juventude, jovens da província moçambicana de Nampula queixam-se da falta de emprego, de habitação e de acesso ao crédito financeiro. O novo coronavírus também é um dos maiores problemas atualmente.
Keywords: #Reporting & Media / Reportagem & Mídia; *tagged; G - Mozambique / Moçambique; G - north / norte; GP - Nampula; L - portuguese / português; employment / emprego; youth / juventude

Niassa: MASC desencoraja envolvimento de jovens nos ataques terroristas - User, Super (2020)
A Fundação MASC - Mecanismo de Apoio a Sociedade Civil, no Niassa, desencoraja o envolvimento de jovens nos ataques terroristas na vizinha província d...
Keywords: #Reporting & Media / Reportagem & Mídia; *tagged; G - Mozambique / Moçambique; G - north / norte; GP - Niassa; L - portuguese / português; civil society / sociedade civil; conflict / conflito; youth / juventude

O sector da educação em Moçambique: do acesso à qualidade epistémica do ensino primário - Mário, Mouzinho; Monjane, Celso M.; Santos, Ricardo (2020)
Desde os primeiros anos de independência nacional, em 1975, o objectivo central da política educativa de Moçambique tem sido o de assegurar que todas as crianças em idade escolar tenham acesso à escola e nela permaneçam até concluírem a educação básica. Na prossecução deste objectivo, a expansão do acesso ao ensino primário foi realizada com relativo sucesso, uma vez que já se alcançou uma taxa líquida de cobertura escolar de quase 100%. Contudo, o impressionante aumento das taxas de escolarização não tem sido acompanhado por uma correspondente melhoria da qualidade da aprendizagem, havendo, em relação a este aspecto, sinais preocupantes de um retrocesso considerável. Partindo desta observação, o estudo identifica e analisa as variáveis do contexto institucional por detrás da 'escolarização sem aprendizagem'. Os resultados do estudo apontam para a (i) fraca capacidade do Estado, (ii) excessiva dependência da ajuda externa e (iii) fraco envolvimento e participação das comunidades na gestão das escolas, como sendo os factores de maior influência na fraca qualidade da aprendizagem no ensino primário.
Keywords: *indexed; *tagged; G - Mozambique / Moçambique; L - portuguese / português; citizenship & participation / cidadania e participação; education / educação; government policy / politica governamental; youth / juventude

The education sector in Mozambique: From access to epistemic quality in primary education - Mário, Mouzinho; Monjane, Celso M.; Santos, Ricardo (2020)
Abstract: From the early days of national independence in 1975, the central aim of the educational policy in Mozambique has been to ensure that all school-age children have access to school and can remain there until they have completed their basic education. In the pursuit of this aim, the extension of access to primary education was achieved relatively successfully, given that it reached a net rate of school coverage of almost 100 per cent. However, the impressive increase in school attendance rates has not been accompanied by a corresponding improvement in the quality of learning, and there are worrying signs of a considerable setback in relation to this aspect. Using this observation as a starting point, the study identifies and analyses the variables in the institutional context behind ‘schooling without learning’. The results of the study point to (i) weak state capacity; (ii) excessive dependence on external aid; and (iii) poor community involvement and participation in school management, as being factors with a major influence on the poor quality of education in primary schools.
Keywords: *indexed; *tagged; G - Mozambique / Moçambique; L - english / inglês; citizenship & participation / cidadania e participação; education / educação; government policy / politica governamental; youth / juventude

The Relationship Between Population Growth, Age Structure, Conflict, and Governance in Sub- Saharan Africa - O’Driscoll, Dylan (Institute of Development Studies, Brighton, UK, 2020)
This report addresses the relationship between population growth, age structure, and conflict in Sub-Saharan Africa (SSA). The literature reviewed for this report presents strong evidence that age structure and population growth matter for conflict. There is particularly strong evidence that points to the relationship between young age structure and conflict, although studies that disaggregate types of conflict and characteristics of young age structures (urban, male, etc.) tend to offer more robust findings. Youth bulges in particular have been associated with increased risk of conflict. The general consensus is that, in countries that will continue to experience high rates of population growth and large youth cohorts, the potential for conflict will continue to be elevated. COVID-19 is putting a dent in already weak formal employment and education. Policy responses to the pandemic will have lasting impacts for those most affected, including young people, and should therefore include them in response. The following policy recommendations are made in the literature including Patriarchal gender norms and masculinity contribute to violence and conflict, and thus policies aimed at increasing gender equality help mitigate conflict risk; The prediction that youth bulge is associated with the onset of conflict should encourage policymakers in countries with young age structures to address societal and economic inequality and foster greater inclusion of the younger cohorts into society; and Youth underemployment (and unemployment) remain an issue in SSA; bringing about structural changes that facilitate the transition into the labor market is likely to mitigate the conflict risks associated with youth bulges
Accepted: 2020-11-04T11:13:17Z Publisher: Institute of Development Studies
Keywords: #Reviews & Framing / Revisões e Organização; *tagged; G - Rest of the World / Resto do Mundo; L - english / inglês; conflict / conflito; gender / género; youth / juventude

Colocar o sistema financeiro ao serviço dos pobres e das PME - Osman, Abdul Magid; Osman, Djamila Pontes (2020)
O esforço de inclusão financeira alcançou resultados positivos, tendo a bancarização da população moçambicana aumentado consideravelmente, em particular depois de 2011-12. Contudo, o impacto económico e social foi limitado, considerando que a produtividade agrícola se tem mantido baixa e os níveis de pobreza ainda são elevados. A doutrina neoliberal na esfera económica, a sua expressão nas políticas monetárias restritivas e a fraqueza do sistema de democracia multipartidária têm sido factores institucionais de constrangimento ao desenvolvimento económico e social. Consequentemente, este estudo propõe algumas medidas de reforma institucional para se expandir o crédito aos agricultores familiares de subsistência, às pequenas e médias empresas, à população em geral e às famílias de rendimento mais baixo em particular. Os jovens poderão beneficiar de créditos mais acessíveis para habitação. Os produtores familiares rurais também necessitam de um suporte sistémico público.
Keywords: *indexed; *tagged; G - Mozambique / Moçambique; L - portuguese / português; financial inclusion / inclusão financeira; fiscal policy / política fiscal; monetary policy / política monetária; poverty / pobreza; private sector / setor privado; youth / juventude

Putting the financial system to work for the poor and SMEs - Osman, Abdul Magid; Osman, Djamila Pontes (2020)
Abstract: The financial inclusion effort achieved positive results, with the number of Mozambicans having access to banking services increasing considerably, particularly after 2011–12. However, the economic and social impact was limited, considering that farm productivity has remained low and poverty levels are still high. The neoliberal doctrine in the economic sphere, its expression in the restrictive monetary policies, and the weakness of the multi-party democracy system have been institutional factors restricting economic and social development. Consequently, this study proposes some institutional reform measures to expand credit to family subsistence farmers, small and medium-sized enterprises, the population in general, and low-income families in particular. Young people could benefit from more accessible housing loans. Rural family farmers also need systemic, public support.
Keywords: *indexed; *tagged; G - Mozambique / Moçambique; L - english / inglês; financial inclusion / inclusão financeira; fiscal policy / política fiscal; monetary policy / política monetária; poverty / pobreza; private sector / setor privado; youth / juventude

Narrativas Alternativas: Lançamento Do Álbum Moçambique Yethu! #stopviolenciaextremista - MASC, Fundação (Fundação MASC, 2020)
Desde o final de 2017, Cabo Delgado, tem sido palco de violentos ataques de grupos […]
Keywords: *tagged; G - Mozambique / Moçambique; G - north / norte; L - portuguese / português; civil society / sociedade civil; conflict - violent extremism / conflito - extremismo violento; conflict / conflito; youth / juventude

The Mozambique Conflict and Deteriorating Security Situation - Bukarti, Bulama; Munasinghe, Sandun (Tony Blair Institute for Global Change, 2020)
For almost three years, the ISIS-affiliated extremist group Ansar al-Sunna has spearheaded an insurgency in Mozambique’s northern province of Cabo Delgado. In recent months the situation in Cabo Delgado has deteriorated significantly and violent attacks are now frequent. Militants have begun to target military positions having previously focused on civilian targets. It is a sign that the group is growing in resilience, operational capacity and confidence. From its first few attacks in Mocimboa de Praia in late 2017, the group now launches more than 20 attacks every month in an insurgency that covers nine major towns and districts along the Cabo Delgado coast. A battle for the town of Macomia at the end of May demonstrates the group’s organisational capacity and ambition as well as an escalation in the government’s counter-offensive efforts. On 30 May 2020, government forces engaged Ansar al-Sunna militants in one of the largest counter-terrorism operations to date, resulting in the reported deaths of 78 insurgents, including two of the group’s leaders. The extent to which this will impact Ansar al-Sunna’s operations and long-term ambitions remains to be understood.
Keywords: *tagged; G - Mozambique / Moçambique; G - north / norte; GP - Cabo Delgado; L - english / inglês; conflict - violent extremism / conflito - extremismo violento; conflict / conflito; youth / juventude

Our voices must be heard – Youth hubs discuss economic exclusion - Matsinhe, Julião (Centro para a Democracia e Desenvolvimento, 2020)
Youth hubs discuss economic exclusion. Unemployment was singled out as the most pressing challenge that young people face. As an answer to unemployment, these young people highlighted that education must equip students with relevant skills to be innovative and entrepreneurs, and to be competitive in the labor market.
Keywords: *indexed; *tagged; G - Mozambique / Moçambique; G - north / norte; L - english / inglês; social inclusion & exclusion / inclusão e exclusão social; youth / juventude

Os Desafios da Expansão do Ensino Superior e a Formação do Capital Humano em Moçambique - Batone, Domingos Carlos (2020)
This research entitled “The Challenges of Expanding Higher Education and the Formation of Human Capital in Mozambique”, analyzes the quality, sustainability and democratization of Higher Education and its influence on the development of human capital. However, the results of this study show that despite the increase in the number of Universities, in several developing countries, such as Mozambique, many of the poorest people remain in the rural sector and tend to continue there for several decades, with the need to bring establishments closer together teaching communities. To reduce poverty, it is necessary to do something for this sector, the right thing to do is to educate the population until reaching a higher level and generate human capital. Based on the consulted literature, using bibliographic research, documentary research and relying on the Human Capital Theory, it was found that the experiences of successful countries depended on social stability, and this cannot be maintained when large portions of the population fall behind in education. Therefore, higher education in these areas cannot be just a way out, it must also be a way of ascending life to obtain more income and consequently foster development. In this sense, the conclusion was reached that higher education is the best way to reduce social inequalities and poverty in Mozambique, however, the sustainability, quality and democracy of higher education must be preserved.
Publisher: Unpublished
Keywords: *tagged; G - Mozambique / Moçambique; L - portuguese / português; access to services / acesso a serviços; education / educação; poverty / pobreza; youth / juventude

Vampiros, Jihadistas e Violência Estrutural em Moçambique: Reflexões sobre Manifestações Violentas de Descontentamento Local e as suas Implicações para a Construção da Paz - Weimer, Bernhard (Instituto de Estudos Sociais e Económicos (IESE), 2020)
Este ensaio, escrito em Março de 2018, procura explicar, numa perspectiva histórica, ataques violentos recentemente perpetrados contra instituições locais e representantes do Estado moçambicano. São usados estudos de caso de três províncias moçambicanas, aos quais se acrescentam casos históricos de ataques armados com padrões e alvos semelhantes. Com base em investigação documental, entrevistas e análise da literatura de Antropologia e Economia Política, são identificadas três causas principais dos conflitos locais – todos eles com os seus contextos e narrativas específicos: em primeiro lugar, a economia política com raízes históricas, dominada pela Frelimo, lida com o descontentamento e a divergência de forma autoritária e muitas vezes violenta, ou, nas palavras do antropólogo Bjørn Bertelsen, com «guerra como governação»; Em segundo lugar, a Ordem de Acesso Limitado firmemente estabelecida em Moçambique produz a exclusão socioeconómica de intervenientes e interesses sociais, económicos e políticos locais, nomeadamente quando se relaciona com extracção de recursos naturais; e um terceiro factor é uma perspectiva de que «não há futuro» da juventude moçambicana, a maioria demográfica. Presa numa idade da espera (waithood, Alcinda Honwana), esta juventude está alienada das suas comunidades e culturas locais, mas não foi absorvida pela sociedade e pela economia. Isso torna os jovens do sexo masculino vulneráveis a influências globais e às promessas dos seus pares, às vezes relacionados com redes de pensamento religioso radical e de criminalidade. O ensaio analisa também a medida em que a parte nordeste de Moçambique, com os seus enormes investimentos numa indústria de Gás Natural Liquefeito (GNL), é vulnerável à influência do islamismo militante. O estudo termina com sugestões para enfrentar os conflitos locais, que surgem numa altura em que a «guerra» de longa data entre o Governo da Frelimo e a Renamo está a ser negociada visando um acordo político.
978-989-8464-46-0
Keywords: *tagged; G - Mozambique / Moçambique; G - Nacala; G - north / norte; GD - Mocímboa da Praia; GP - Cabo Delgado; GP - Nampula; GP - Niassa; L - portuguese / português; conflict - violent extremism / conflito - extremismo violento; conflict / conflito; governance / governação; social inclusion & exclusion / inclusão e exclusão social; youth / juventude

Mozambique Annual Report 2020: Responding to a Year of Crisis - Wojnar, Andrea M; Lomelin, Jessica; Baker, Daniel; Salu, Karlina; Macangira, Assane; Manjate, Epidauro (UNFPA, 2020)
In the case of Mozambique, the pandemic came on the heels of two destructive cyclones that had devastated large parts of the country in 2019 and whose consequences were still being felt. In northern Mozambique, increasing violence in Cabo Delgado province resulted in a surge of internally displaced persons into local communities in Cabo Delgado, Nampula and Niassa provinces. With host communities ill equipped to meet the needs of those displaced, this population movement created a new humanitarian crisis in the midst of the pandemic. Like all of our governmental, civil society and donor partners, the resilience of UNFPA was tested, and we had to adjust quickly after the first case of COVID-19 was confirmed in March and the Government declared a state of emergency. At the most basic level, women continued to get pregnant and babies were still being born, even in the middle of a pandemic. Addressing the needs of adolescent girls and young women could not be put on hold. Helping to meet the needs of the symbolic target of UNFPA’s work – “the 10-year-old girl” – could not wait until she was 11. Helping to meet her aspirations for the future, advocating and working for her growth and self-fulfillment as a woman leading a healthy, productive and violence-free life – these could not wait a year.
Keywords: G - Mozambique / Moçambique; Health PEA; L - english / inglês; gender / género; health - COVID-19 / saúde – COVID-19; health / saúde; youth / juventude